Incremental Frequent Pattern Mining using Graph based approach - Patel, Sanjay; Kotecha, Dr. Ketan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Extracting useful information from huge amount of data is known as Data Mining. It happens at the intersection of artificial intelligence and statistics. It is also defined as the use of computer algorithms to discover hidden patterns and interesting relationships between items in large datasets. Candidate generation and test, Pattern Growth etc. are the common approaches to find frequent patterns from the database. Incremental mining is a crucial requirement for the industries nowadays. Many tree based approaches have tried to extend the frequent pattern mining as an incremental approach, but most of the research was limited to interactive mining only. Here, instead of tree based approach, graph based approach is presented which also gives good results for incremental mining. Â 